Effectiveness of “Sumut-History” Website Platform on Digital Literacy and Cultural Awareness of Elementary School Students - Karina Wanda; Anik Ghufron; Ibnu Syamsi (Proceeding of the International Conference on Social Sciences and Humanities Innovation, 2025)
This study investigates the effectiveness of the “Sumut-History” website platform in enhancing digital literacy and cultural awareness among elementary school students. Employing a quantitative approach with a quasi-experimental design, the research involved 124 fifth-grade students in Medan, North Sumatra, divided into experimental and control groups. Data were collected using digital literacy tests, cultural awareness questionnaires, and classroom observations. The findings reveal that students who utilized the platform demonstrated significant improvement in digital literacy, particularly in critical thinking, information evaluation, and digital ethics. In addition, the integration of local cultural content through digital storytelling and interactive multimedia significantly increased students’ cultural awareness, including their understanding of local heritage and sense of identity. The study also highlights a positive synergy between digital literacy and cultural awareness, suggesting that both competencies can be developed simultaneously through contextualized digital learning. These results indicate that web-based platforms integrating local cultural narratives can serve as effective educational tools in primary education. The study contributes to the advancement of technology-enhanced learning and supports the promotion of culturally responsive digital education.